Efficiency of Stereotactic Conformal Radiotherapy in Lung Metastases with Active Breathing Control - Olga Yu. Anikeeva, PhD; Oxana A. Pashkovskaya; Petr V. Filatov; Elena A. Samoilova, PhD (International Journal of Biomedicine, 2013)
Twenty four patients with lung metastases underwent radiosurgery treatment between October 2010 and December 2012. Stereotactic conformal high-dose radiation therapy with Active Breathing Control (ABC) was conducted using the volumetric modulated arc therapy (VMAT) technique. The median overall follow-up was 18 months (range 6-24 months), overall survival was 75%, and local control rate was 92%. The median time to progression was 4 months (range 1-18 months).There have been no cases of leucopenia, radiation esophagitis, mediastinitis or severe acute radiation pneumonitis. The late radiation effects Grade 2, according to the LENT SOMA scales, was observed in one patient (4%). The results of this study indicate that the usage of the stereotactic high-dose radiation therapy with ABC is safe and effective in the treatment of lung metastases.